Do Diagnostic Nerve Blocks Affect the Starting Dose of Botulinum Neurotoxin Type A for Spasticity? A Case-Control Study - Mirko Filippetti; Stefano Tamburin; Rita Di Censo; Roberto Aldegheri; Elisa Mantovani; Stefania Spina; Marco Battaglia; Alessio Baricich; Andrea Santamato; Nicola Smania; Alessandro Picelli (Toxins)
One of the aims of diagnostic nerve blocks is to identify the overactive muscles that lead to a specific spasticity pattern. However, to date, there is no evidence on how nerve blocks may affect botulinum neurotoxin-A (BoNT-A) dose in patients with spasticity. This case-control study aims to assess the role of diagnostic nerve block in defining BoNT-A starting dose at first treatment. Patients with upper and lower limb spasticity treated for the first time with BoNT-A were retrospectively divided into two groups: Group 1 (n = 43) was evaluated with clinical assessment and diagnostic nerve block; Group 2 (n = 56) underwent clinical assessment only. Group 1 was injected with higher BoNT-A doses in some muscles (i.e., flexor digitorum profundus, soleus), and received a higher BoNT-A cumulative dose with a larger number of injected muscles for some spasticity patterns (i.e., “clenched fist”, “flexed fingers”, “adducted thigh”). Diagnostic nerve block may help the clinician to optimize and personalize the BoNT-A dose since the first BoNT-A treatment.